Islamic Development Concept: A Proposal For Betterment of Muslim Ummah in the Post-Pandemic Episode - Sebastian Herman (Universitas Alma Ata, 2021)
Islamic civilization was the pearl of the world with multidimensional aspects of achievements, especially during the Dark Age of West civilization. In stark contrast to this, the Muslim world nowadays is experiencing a marginalized society on this planet. The majority of Muslim countries are backward educationally, socially, economically, and politically. Furthermore, the world nowadays is suffering an economic crisis due to the impact of the COVID-19 pandemic. This study tries to investigate the economic development concept from an Islamic perspective, compare it with current data on OIC member countries and provide recommendations for policymakers to stave the disaster off. The study adopts a quantitative approach in form of a literature review, discourse, and critical content analysis. It found that economic development in an Islamic perspective can be defined as a multidimensional process to improve welfare, in both material and spiritual aspects. However, In reality, OIC member countries have potentials and obstacles for growth. Strengthening the education sectors, infusion of Islamic values, support SMEs' development with ICT are some recommended policies. The main contribution of this study is to assess the current condition of Muslim Ummah represented by OIC member countries, by the development concept of Islam and deliver some policies for the betterment of the ummah.